2020
DOI: 10.1177/2053369120971427
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle practices and menopause-related symptoms among women in rural communities of Ado-Ekiti local government area, Nigeria

Abstract: Objective Lifestyle modification is consistently recommended for healthy living during menopause; nonetheless, there is paucity of data on menopausal experiences and lifestyle practices of women in rural communities of Nigeria. This study assessed the lifestyle practices of menopausal women, their experiences of menopause-related symptoms and the influence of lifestyle practices on their experiences of menopause-related symptoms. Method A descriptive cross-sectional design was used in this study. Systematic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
2
3
0
Order By: Relevance
“…Further findings showed that about three-quarters of the women still experience painful sexual intercourse. This is comparable to previous studies that reported pain as one of the most common problems among menopausal women [ 19 30 31 ] and another study that reported that about two-thirds of their study participants experienced pain during sexual intercourse [ 32 ]. This, however, goes contrary to the findings in a study where very few of their respondents (17.1%) reported experiencing pain during sexual intercourse [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Further findings showed that about three-quarters of the women still experience painful sexual intercourse. This is comparable to previous studies that reported pain as one of the most common problems among menopausal women [ 19 30 31 ] and another study that reported that about two-thirds of their study participants experienced pain during sexual intercourse [ 32 ]. This, however, goes contrary to the findings in a study where very few of their respondents (17.1%) reported experiencing pain during sexual intercourse [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…The purpose of this study was to assess the sexual health status and its determinants among menopausal women. The respondent’s mean age at menopause in this study is comparable to other previous studies [ 19 20 ]. The sexual history shows that the majority of the respondents experienced natural menopause, which is similar to a study where it was found that the majority of the women experienced natural menopause [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…According to the results of the current study, the severity of perimenopausal symptoms and women's lifestyle behaviors are strongly negatively correlated. Concerning perimenopausal symptoms, this research stated that more than one third of perimenopausal women reported moderate severity of perimenopausal symptoms, as has been seen in the study of Olowokere et al (2021). But these outcomes were in opposition to Farahat, El Esergy, and El Shopaky's (2019) research that demonstrated that severe perimenopausal symptoms were present in over fifty percent of the subjects.…”
Section: Discussionmentioning
confidence: 78%
“…Self-developed surveys are multidimensional and quick to administer, but lack validity and reliability. [ 6 ] In order to produce valid and reliable data, studies administered lists of validated questionnaires such as Depression, Anxiety and Stress Scale-21 to measure distress, Body Shape Questionnaire to measure body image issues, and Woman's Health Questionnaire for menopausal quality of life. [ 33 34 ] Often these questionnaires are administered in combination with recall methods such as 24-h recall and Global Physical Activity Assessment Questionnaire for assessing dietary and activity status.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 ] Few studies have used self-developed questionnaires for preliminary assessment only, as they suffer from fundamental limitations like lack of validity and reliability. [ 6 ] Other valid and reliable methods such as comprehensive lists of valid questionnaires and recall methods are resource-intensive, time-consuming, and complex to interpret in a resource-constrained clinical setting. [ 7 8 ] We aimed to develop and validate an easy-to-administer comprehensive evaluation tool to assess women-centric risk factors for weight gain, weight-related perceptions, and practices of middle-aged women.…”
Section: Introductionmentioning
confidence: 99%